Labour market of the countries of the Central and Eastern Europe bloc - an analysis of the dynamics and perspectives of changes - Balcerowicz-Szkutnik, Maria (Rynek pracy państw bloku Europy środkowo-wschodniej – analiza dynamiki i perspektywy zmian, 2015)
One of the aspects of progressing globalisation processes is the change in the structure of labour market, especially in the employment and unemployment level. The scale of these changes is indirectly dependent on the potential of the labour resources in the local (national) labour markets. The main objective of the paper is to indicate the similarities and differences in changes in parameters that describe the labour market in selected states of the EU with reference to globalisation processes. The paper also makes an attempt to define (on the basis of simple statistical methods) the future reaction of the labour market, in the form of forecasts of selected parameters describing its condition. Detailed analyses include discussion on the dynamics of changes in occupational activity factor and employment rates. They include the dynamics of changes in employment structure in terms of the progressing process of ‘servicisation’, and the aforementioned forecasts are constructed for these parameters. The time range of the research includes the period 2004-2013, and the prognosis for 2014, 2015 and 2016; the selected group of countries includes countries of Central and Eastern Europe belonging to the European Union
Ekonometria = Econometrics, 2015, Nr 1 (47), s. 32-43
Keywords: labour market; occupational activity; employment rate; servicisation; bloc of statesof Central and Eastern EU; rynek pracy; aktywność zawodowa; zatrudnienie; serwicyzacja; blok państw Europy Środkowo-Wschodniej